2017
DOI: 10.1109/tkde.2017.2720601
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Sudden and Gradual Drifts in Business Processes from Execution Traces

Abstract: Business processes are prone to unexpected changes, as process workers may suddenly or gradually start executing a process differently in order to adjust to changes in workload, season or other external factors.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
99
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(101 citation statements)
references
References 32 publications
2
99
0
Order By: Relevance
“…is observation is aligned with previous studies in the eld of process mining, which have shown that concept dri s are common in the control ow of business processes [24,29,30]. Techniques for automated detection and characterization of process control-ow dri s from event logs and event streams are available [24,29,30]. Researchers and practitioners using predictive monitoring methods should consider applying these detection methods, as well as standard statistical tests on the features extracted, to ensure that there is no dri present, which could a ect the performance of the predictive models.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…is observation is aligned with previous studies in the eld of process mining, which have shown that concept dri s are common in the control ow of business processes [24,29,30]. Techniques for automated detection and characterization of process control-ow dri s from event logs and event streams are available [24,29,30]. Researchers and practitioners using predictive monitoring methods should consider applying these detection methods, as well as standard statistical tests on the features extracted, to ensure that there is no dri present, which could a ect the performance of the predictive models.…”
Section: Resultssupporting
confidence: 90%
“…Also, although the hyperparameters were optimized using a state-of-the-art hyperparameter optimization technique, it is possible that using more iterations for optimization or a di erent optimization algorithm, other parameter se ings would be found that outperform the se ings used in the current evaluation. Furthermore, the generalizability of the ndings is to some extent limited by the fact that the experiments were performed on a limited number of prediction tasks (24), constructed from nine event logs. Although these are all real-life event logs from di erent application elds that exhibit di erent characteristics, it may be possible that the results would be di erent using other datasets or di erent log preprocessing techniques for the same datasets.…”
Section: Threats To Validitymentioning
confidence: 99%
“…A drift is a statistically significant change observed in an event log or in a stream of traces. In [21,22], we introduced a drift detection technique where the basic idea is to perform a statistical test over the distributions of partially-ordered runs observed in two consecutive time windows sliding over a log or a stream of traces. A run represents a set of traces that are equivalent to each other modulo a concurrency relation between event types.…”
Section: Application To Process Drift Detectionmentioning
confidence: 99%
“…A significant challenge for adopting concept drift for process mining is to represent behavior in a time-dependent way. The approach reported in [14] uses causal dependencies and tracks them over time windows. The specific challenge is to not only spot a drift but also to classify it.…”
Section: Motivating Examplementioning
confidence: 99%
“…Approaches like ProDrift [14] and Graph Metrics on Process Graphs [22] put an emphasis on requirement R1. The evaluation of ProDrift in [14] shows that two types of drifts are found with high accuracy (sudden and gradual drifts), hence partly addressing requirement R2; note that the authors report high sensitivity of the technique to the choice of the method parameters. The approach relies on the automated detection of changes in business process executions, which are analyzed based on causal dependency relations studied in process mining [24].…”
Section: Requirementsmentioning
confidence: 99%